Measurement of perceived and expected inflation on the basis of consumer survey data - Łyziak, Tomasz (Bank for Internat. Settlements, 2010)
This paper discusses measurement techniques used in the literature to quantify inflation perception and expectations on the basis of qualitative survey data. Description of quantification methods and assessment of their strengths and weaknesses is supplemented with an overview of direct measures of consumer inflation expectations in the European Union quantified with a number of techniques. Except presenting quantification methods, constraints in their interpretation and their results, the paper describes how direct measures of inflation expectations are used in central banks nowadays.
Keywords: Arbeitspapier; Graue Literatur; Inflationserwartung; Messung; Befragung; EU-Staaten